Petrocephalus leo, a new species of African electric fish (Osteoglossomorpha: Mormyridae) from the Oubangui River basin (Congo basin) - Lavoué, Sébastien (Zootaxa, 2016)
A new species of the African weakly electric fish genus Petrocephalus (Osteoglossomorpha: Mormyridae: Petrocephalinae) is described from the Oubangui (Ubangi) River basin, the principal right-bank tributary of the Congo River. Petrocephalus leo sp. nov. is one of the most distinctive species of Petrocephalus as it combines (among other characteristics) the absence of electroreceptive rosettes on the head with a unique melanin pattern. Only four other species of Petrocephalus lack all electroreceptive rosettes: Petrocephalus microphthalmus, Petrocephalus haullevillii, Petrocephalus schoutedeni, and Petrocephalus zakoni. Petrocephalus leo sp. nov. can be distinguished from these four species in having a distinctive black mark at the base of the pectoral fins (versus absent in P. microphthalmus, P. haullevillii and P. schoutedeni) and no subdorsal black mark (versus present in P. zakoni). A phylogenetic analysis using mitochondrial cytochrome b gene sequences shows haplotypes of P. leo sp. nov. are distinct, but are unexpectedly nested within P. zakoni haplotypes, making this latter species paraphyletic. To investigate this conflict between morphology and mitochondrial cytochrome b, a nuclear marker, the first intron of the gene coding for the S7 ribosomal protein, was sequenced. The presence of four diagnostic indels between P. zakoni and P. leo sp. nov. sequences supports the reciprocal monophyly of these two species. This is the first reported case of conflict between morphology and mitochondrial phylogeny within the genus Petrocephalus. Finally, three species of Petrocephalus are reported for the first time from the Oubangui region bringing the total of Petrocephalus species in this region to 12.